"The merits and demerits of Ibsen’s great play": the reception of the Novelty Theatre Company matinée performance A doll’s house, Theatre Royal, Brighton England, June 20th 1889 - Wolfe, Jill Farleigh (Nordlit, 2015)
“Merits and Demerits of Ibsen’s great play”: The Reception of a performance of A Doll’s House by the Novelty Theatre Company at The Theatre Royal Brighton England June 20th 1889. This article discusses the reception of a matinée performance of Henrik Ibsen’s A Doll’s House on June 20th 1889 at The Theatre Royal Brighton England. This would be the only performance mounted outside London of the original Novelty Theatre Company’s three week production in English as translated by William Archer. Resources from the Brighton Archives which have not been examined before are used, including theatre reviews from local newspapers: The Brighton Herald, The Brighton Examine, The Brighton Times, and The Argus. Coverage of the performance in these newspapers illustrates how the battle between supporters and detractors of Ibsen’s drama continued outside London. Their reviews of the matinée offer valuable insights into the reception of A Doll’s House, not only by theatre critics but a specific audience on a particular English provincial, The Theatre Royal Brighton. Such newspaper accounts allow us to get a much more detailed perspective on Ibsen and the intellectual issues that his drama raised for a provincial audience in Brighton England. The article examines in detail positive responses to Ibsen´s play and the social issues that both shocked and fascinated his audience.